Impact of Globalization on Entrepreneurial Risk - Abeyrathna, K. G. N. W. (AMC Indian Journal of Entrepreneurship, 2021)
Globalization refers to the process of integration of the world into one huge market whereby it provides several opportunities to several people with the removal of all trade barriers among countries. Thus, economic activities of the world are influenced by globalization processes and globalization transfer. The risk for entrepreneurs is affected by economic crisis, political crisis, and technology crisis. Globalization has influenced blue-chip firms, small-scale businesses, and entire business world. This study assesses the impact of globalization on small and medium entrepreneur’s risk, focusing on Colombo districts’ small and medium apparel as well as tourist restaurants. Past literature had revealed the relationship between globalization and entrepreneurship using secondary and primary data and these used several models which had effectively proven the relationship of globalization and entrepreneur risk. A sample frame of 250 was selected using non- probabilistic sampling technique. 150 small and medium apparel enterprises were selected from the Colombo district and 100 small and medium tourist restaurants were also selected from the Colombo district. Face to face interview method was used for primary data collection. Secondary data were collected from reports of census and statistics department, and central bank. As a research model, canonical correlation and Manova were used to present the result of the data. SPSS and MS Excel were used to analyze the collected data. Apropos of the main findings of the study, there exist a positive correlation between globalization and entrepreneurial risk. Hence, it is imperative (sine qua non) for entrepreneurs to avoid risk factors of globalization due to the fact that risk causes huge damage to business by keeping continuous savings, joining ventures, issuing shares, and considering innovative investments as are the solutions to avoid the risk of globalization. This research contributes new knowledge to mitigate globalization related risks of entrepreneurship.